Brian Britt. Religion Around Walter Benjamin. The Pennsylvania State UP, 2022. - Doris McGonagill (Studies in 20th & 21st Century Literature, 2023)
Review of Brian Britt. Religion Around Walter Benjamin. The Pennsylvania State UP, 2022. xvii + 233 pp.
Keywords: Walter Benjamin; religious and intellectual history; Modernism; Germany; 20th century